Eight cousins, or, The Aunt Hill - Alcott, Louisa May, 1832-1888. (New York, N.Y. : Gramercy books, 1995)
Orphaned Rose Campbell finds it difficult to fit in when she goes to live with her six aunts and seven mischievous boy cousins.
Sequel: Rose in bloom.
"Yearling book."
Keywords: Orphans -- Fiction; Cousins -- Fiction; Family life -- Fiction